DC Voltage Control Strategy for CHB-STATCOM during Capacitive-Inductive Load Transition - Weiming Zhao; Yong Wang; Bo Zhao (Institute of Advanced Engineering and Science, 2012)
Fluctuation of DC capacitor voltage of CHC-STATCOM(Cascaded H-Bridge Converter Based STATCOM) during capacitive-inductive load transition affects the dynamic response of the equipment and, with combination of other factors like of the switching devices, can degrade the stability of the equipment. This paper illustrates the cause ofthe voltage fluctuation and proposes a novel and practical control strategy to suppress it. A simulation was conducted to testify its effectiveness. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1570